What is taking place in science classrooms?: a case study analysis of teaching and learning in seventh-grade science of one Alabama school and its impact on African American student learning - Norman, Lashaunda Renea (Kansas State University, 2013)
This qualitative case study investigated the teaching strategies that improve science learning of African American students. This research study further sought the extent the identified teaching strategies that are used to improve African American science learning reflect culturally responsive teaching. Best teaching strategies and culturally responsive teaching have been researched, but there has been minimal research on the impact that both have on science learning, with an emphasis on the African American population. Consequently, the Black-White achievement gap in science persists. The findings revealed the following teaching strategies have a positive impact on African American science learning: (a) lecture-discussion, (b) notetaking, (c) reading strategies, (d) graphic organizers, (e) hands-on activities, (f) laboratory experiences, and (g) cooperative learning. Culturally responsive teaching strategies were evident in the seventh-grade science classrooms observed. Seven themes emerged from this research data: (1) The participating teachers based their research-based teaching strategies used in the classroom on all of the students’ learning styles, abilities, attitudes towards science, and motivational levels about learning science, with no emphasis on the African American student population; (2) The participating teachers taught the state content standards simultaneously using the same instructional model daily, incorporating other content areas when possible; (3) The participating African American students believed their seventh-grade science teachers used a variety of teaching strategies to ensure science learning took place, that science learning was fun, and that science learning was engaging; (4) The participating African American students genuinely liked their teacher; (5) The participating African American students revealed high self-efficacy; (6) The African American student participants’ parents value education and moved to Success Middle School district for better educational opportunities; and (7) Teachers were not familiar with the term “culturally responsive teaching,” but there was evidence that several aspects of it were present in the seventh-grade science classroom environment. Critical Race Theory (CRT) was the framework for analysis and interpretation of this research study. The findings support the following tenets of CRT: (a) racism is normal, (b) interest-convergence or colorblindness, (c) contextual-historical analysis, (d) storytelling or counterstorytelling, and (e) social transformation. These findings indicate that racial inequalities remain an issue in the underachievement of African Americans and may be the solution to improving science learning of African Americans. The outcome of this study contributes to the limited research on utilizing culturally responsive teaching along with best teaching strategies to improve academic achievement of African American students, and CRT exposes the issues that contribute to the Black-White achievement gap in science widening.
Keywords: Culturally responsive teaching; Critical race theory; African American; Science teaching strategies; Black-White achievement gap; Middle school science; African American Studies (0296); Middle School education (0450); Science Education (0714)